The Relationship Between Mathematics Anxiety and Problem-Solving Skills among Junior High School Students in Indonesia - Rissa Isabella Taruli Marpaung; Justin Eduardo Simarmata (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2026)
Mathematics anxiety is a well-documented affective factor that negatively impacts students’ performance and engagement in mathematics. This study explores the relationship between mathematics anxiety and problem-solving skills among junior high school students in Indonesia. A total of 35 students from Grades 7 and 8 at SMP Sangkara in Medan participated. Mathematics anxiety was measured using a 20-item Likert scale (lower scores indicate higher anxiety), while problem-solving ability was assessed through a five-question open-ended test scored on a 4-point rubric. Descriptive statistics indicated moderate to high mathematics anxiety (M = 33.31, SD = 6.59) and low to moderate problem-solving ability (M = 8.06, SD = 4.33). Pearson correlation analysis revealed a strong, statistically significant positive relationship (r = 0.774, p < 0.001), showing that higher anxiety corresponded to lower problem-solving performance due to the reverse-coded anxiety scale. These findings underscore the importance of addressing affective challenges in mathematics instruction to enhance students’ problem-solving competence.